Currency crisis and external fragility: a Minskyan interpretation applied to the Brazilian economy between 1999 and 2013 - Rocha Sarto, Victor Hugo; Togeiro de Almeida, Luciana (Nova Economia, 2016)
This work has two goals. The first one is to develop an interpretation for open economies founded on Minsky’s financial fragility hypothesis about the process of a currency crisis and its determinants. The deterioration of an economy’s external financial structure is identified as the reason for the increase of its crisis susceptibility. With this approach, we create external fragility indexes intending to measure an economy’s crisis susceptibility. Our second objective is to evaluate the Brazilian external fragility between 1999 and 2013 using the index and the interpretation previously developed. The results suggest that Brazilian’s external fragility suffered a gradual and significant decrease and tends to follow stable trend in the coming years.